Analisis Pengaruh Tekanan Uap Inlet Turbine terhadap Output Daya - Jilal Lasmana; Dani Rusirawan (Universitas Batanghari Jambi, 2026)
This study aims to analyze the impact of steam inlet pressure variations on the power output of steam turbines in modern power plant systems. The methodology includes thermodynamic calculations based on operating data, evaluation of inlet–outlet enthalpy using steam tables, and power output estimation considering turbine isentropic efficiency. The results indicate that increasing the inlet pressure toward its design value enhances the enthalpy drop by 12–18% and improves turbine power output by 8–15%. Conversely, a reduction in inlet pressure significantly decreases power output due to reduced expansion potential and increased moisture content in the turbine’s final stages. This study highlights the importance of maintaining stable and optimal steam inlet pressure to ensure efficient and reliable operation of modern steam power plants.